2011
DOI: 10.3892/or.2011.1307
|View full text |Cite
|
Sign up to set email alerts
|

Pleural lavage with distilled water during surgery for esophageal squamous cell carcinoma

Abstract: Abstract. This study aimed to investigate cytocidal effects of hypotonic shock on esophageal squamous cell carcinoma (ESCC) cell lines, and to apply pleural lavage with distilled water to surgery for ESCC. Three human ESCC cell lines, TE5, TE9 and KYSE170 were exposed to distilled water, and morphological changes in ESCC cells were closely observed under a differential interference contrast microscope connected to a high-speed digital video camera. Further, serial cell volume changes after hypotonic shock were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Furthermore, we reincubated these cells after they had been exposed to DW and found that the decrease observed in the number of cells in each of the three gastric cancer cell lines depended on the time for which they had been exposed to DW. Similar findings have been reported in esophageal and pancreatic cancer cells [17, 18]. These results suggest that hypotonic shock could be applied for the treatment of dissemination from gastric cancer by using a peritoneal injection of hypotonic solution.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, we reincubated these cells after they had been exposed to DW and found that the decrease observed in the number of cells in each of the three gastric cancer cell lines depended on the time for which they had been exposed to DW. Similar findings have been reported in esophageal and pancreatic cancer cells [17, 18]. These results suggest that hypotonic shock could be applied for the treatment of dissemination from gastric cancer by using a peritoneal injection of hypotonic solution.…”
Section: Discussionsupporting
confidence: 88%
“…RVD was shown to occur after hypotonicity-induced cellular swelling and has been attributed to the activation of ion channels and transporters, which cause K + , Cl − , and H 2 O effluxes, ultimately leading to cell shrinkage [26, 27]. Similar phenomena have been reported in esophageal and pancreatic cancer cells [17, 18]. We could not use NPPB, which blocks multiple types of chloride channels, in the present study because of its neurotoxicity in vivo .…”
Section: Discussionmentioning
confidence: 80%
“…The efficacy of pleural lavage with distilled water during surgery for esophageal squamous cell carcinoma was proposed from the cytocidal effects of hypotonic shock on tumor cells [27]. It is also used as an alternative agent for wound cleansing.…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was then discarded, isotonic NaCl solution was added to the pelleted cells, and the suspended cells were mounted on a coverslip that had been pre-coated with neutralized Cell-Tak (Becton-Dickinson Labware, Bedford, MA, USA) in order to retain them firmly. The coverslip was then placed in a perfusion chamber that had been mounted on the stage of a DIC microscope (ECLIPSE Ti, Nikon, Japan) connected to a video-enhanced contrast (VEC) system (ARGUS-20, Hamamatsu Photonics, Hamamatsu, Japan), and images were continuously recorded by a video recorder, according to a previously described procedure 9 - 12 . Experiments were carried out at room temperature (20-24ºC).…”
Section: Methodsmentioning
confidence: 99%
“…This lavage procedure has been performed on digestive cancer patients, and has cytocidal effects on exfoliated viable cancer cells, thereby preventing peritoneal recurrence. We previously demonstrated the cytocidal effects of this therapy on esophageal, gastric, pancreatic and colorectal cancers in vitro and in vivo 9 - 14 . The efficacy of this therapy for HCC was reported previously, and has been employed during surgery 15 - 16 .…”
Section: Introductionmentioning
confidence: 97%